2011
DOI: 10.3233/prm-2011-0148
|View full text |Cite
|
Sign up to set email alerts
|

The GMFM, PEDI, and CP-QOL and perspectives on functioning from children with CP, parents, and medical professionals

Abstract: Objective: Many outcome measures assess function of children with cerebral palsy (CP), but establishing meaningful clinical change remains challenging. This study explored correlations between subjective status ratings in several functional domains, made by children, parents, and medical professionals. The ratings were compared with three outcome measures in preparation for longitudinal work to establish minimal clinically important change. Method: Children were assessed with the Gross Motor Function Measure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…With regard to the background factors in this present study, the functional GMFCS and MACS levels were significantly associated with feelings about functioning in both the adolescents’ self‐reports and in the caregivers’ evaluation. This was in line with an earlier study, where the researchers found a correlation between subjective well‐being and the severity of the GMFCS and MACS levels . In particular, gross motor function appears to have been a significant factor in several previous studies .…”
Section: Discussionsupporting
confidence: 90%
“…With regard to the background factors in this present study, the functional GMFCS and MACS levels were significantly associated with feelings about functioning in both the adolescents’ self‐reports and in the caregivers’ evaluation. This was in line with an earlier study, where the researchers found a correlation between subjective well‐being and the severity of the GMFCS and MACS levels . In particular, gross motor function appears to have been a significant factor in several previous studies .…”
Section: Discussionsupporting
confidence: 90%
“…In multiple validation studies the CP QOL-Child had good test-retest reliability, construct validity and internal consistency, and Cronbach's alphas of 0.74 to 0.91 [5, 28, 30, 31]. Additionally, parental perceptions provided in the CP QOL-Child correlate with medical professional ratings of patient QOL for children with CP [32]. There is a version of the CP QOL-child that is self-report for children 9 to 12 years old.…”
Section: Methodsmentioning
confidence: 99%
“…Motor difficulties are limited to experiences of the children not only regarding interaction with people, objects, and events, but also regarding how to manipulate objects, repeat actions, control their own bodies and body scheme. Therefore, the child with neuropsychomotor development delay may lose concrete opportunities to evolve his or her abilities, thus causing gaps in the perceptive, cognitive, linguistic, and social areas (5,(7)(8)(9)(10) . So, limitations to explore the environment voluntarily are expected, which can lead to flaws in the sensory input, causing deficit in perceptive areas and damage in the development of language and cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows the effect of the motor condition of CP on several areas of development (3)(4)(5)(6)(7)(8)(9)(10)(11) . In the presence of motor delay, the child may lose opportunities to acquire knowledge, which is influenced by the relationships the child establishes with the environment and with important interferences for general learning and quality of life (5,7,11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation